2018
DOI: 10.1186/s12864-018-4897-1
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analyses of rice (Oryza sativa) genes and non-coding RNAs under nitrogen starvation using multiple omics technologies

Abstract: BackgroundNitrogen (N) is a key macronutrient essential for plant growth, and its availability has a strong influence on crop development. The application of synthetic N fertilizers on crops has increased substantially in recent decades; however, the applied N is not fully utilized due to the low N use efficiency of crops. To overcome this limitation, it is important to understand the genome-wide responses and functions of key genes and potential regulatory factors in N metabolism.ResultsHere, we characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
101
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(102 citation statements)
references
References 96 publications
0
101
0
1
Order By: Relevance
“…For each cell or tissue type, we prepared at least three biological replicates ( Supplemental Table S1). We also included several published small RNA libraries from vegetative tissues: wild-type root (Shin et al 2018), and ddm1a ddm1b double mutant leaf (which we refer to simply as ddm1) and its wild-type control (Tan et al 2016;Tan et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…For each cell or tissue type, we prepared at least three biological replicates ( Supplemental Table S1). We also included several published small RNA libraries from vegetative tissues: wild-type root (Shin et al 2018), and ddm1a ddm1b double mutant leaf (which we refer to simply as ddm1) and its wild-type control (Tan et al 2016;Tan et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Up-regulated expression of AtNRT2.1 stimulated by glucose depends on hexokinase (HXK) activity and pentose phosphate pathway (PPP) metabolism (Lejay et al, 2008;Bussell et al, 2013;de Jong et al, 2014). Overexpression of the hexose transporter STP13 increased the endogenous sucrose content, up-regulated NRT2.2 expression, and enhanced nitrate uptake in Arabidopsis under low-N condition (Schofield et al, 2009). In rice, exogenous sucrose supplementation increased the accumulation of OsNRT2.1, OsNRT2.2, OsNRT2.3, and OsNAR2.1 transcripts (Feng et al, 2011).…”
Section: Osmyb305 Overexpression Altered Carbohydrate Metabolismmentioning
confidence: 99%
“…Extensive transcriptome analyses have been conducted on rice to identify genome-wide changes in gene expression in response to nitrogen starvation (Lian et al, 2006;Cai et al, 2012;Yang et al, 2015;Hsieh et al, 2018;Shin et al, 2018). These studies revealed that in order to contend with nitrogen deficiency, rice must modulate the expression levels of extensive genes involved in N assimilation, C metabolism, root architecture formation, chlorophyll biosynthesis and stress response.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 2542 lincRNA candidates in Populus trichocarpa (P. trichocarpa) [26], nearly 10,000 lncRNAs in maize (Zea mays L.) [27][28][29][30], as well as 682 high-confidence lncRNAs in cassava [31] were identified. In rice, by performing whole-transcriptome strand-specific RNA sequencing (ssRNA-seq), 2224 lncRNAs involved in the reproductive process [32] and 2588 novel putative lncRNA encoding loci under nitrogen starvation were verified [33]. In Brassica, 1885, 1910, and 1299 lncRNAs at the whole genome level were identified for B. napus, B. oleracea, and B. rapa, respectively [34].…”
Section: Capturing Lncrnas In Plantmentioning
confidence: 99%